Characteristics of Pre-Service Teacher’s Spoken Language in Teaching Practice: A Systematic Literature Review - Ratna Muthia; Subyantoro Subyantoro; Haryadi Haryadi (Proceedings of International Conference on Science, Education, and Technology, 2026)
Oral language is an essential component of teachers’ pedagogical competence. As future educators, pre-service teachers need to develop effective oral language skills as part of their teaching practice. This study aims to analyze and synthesize the characteristics of pre-service teachers’ spoken language in teaching practice based on previous research. The study employed a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Articles were identified through searches in Google Scholar, the Education Resources Information Center (ERIC), and Scopus. Following the application of inclusion and exclusion criteria, 17 articles were selected for analysis. The findings indicate several tendencies in pre-service teachers’ spoken language. First, spoken language is predominantly used to manage classroom activities and direct students’ learning through questioning, teacher talk, and directive speech acts. Second, spoken language tends to function as a means of knowledge transmission, as reflected in the prevalence of display questions, factual questions, and Initiation–Response–Evaluation (I-R-E) interaction patterns. Third, the use of language to promote argumentation, negotiation of meaning, and collaborative knowledge construction remains limited. Fourth, pre-service teachers employ code-mixing as a communication strategy to adapt to multilingual classroom contexts. These findings suggest that pre-service teachers have developed the ability to use spoken language for organizing classroom instruction; however, its use in fostering productive academic dialogue still requires further strengthening. This comprehensive overview of the spoken language characteristics of pre-service teachers may serve as a foundation for the development of teacher education programs that place greater emphasis on dialogic learning.